2006
DOI: 10.1097/01.hp.0000180770.63571.19
|View full text |Cite
|
Sign up to set email alerts
|

Radon Concentrations in Elementary Schools in Kuwait

Abstract: Measurements of indoor radon concentrations were performed in 25 classrooms in the capital city of Kuwait from September 2003 to March 2004 using track etch detectors. The investigation was focused on area, ventilation, windows, air conditioners, fans, and floor number. All the schools have nearly the same design. Mean indoor radon concentration was higher for case subjects (classrooms) than for control subjects (locations in inert gas, p < 0.001). The mean alpha dose equivalent rate for case subjects, 0.97 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…The mean radon concentrations in elementary schools in Kuwait have been measured and found 17 Bq m −3 after subtracting the control (Maged 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The mean radon concentrations in elementary schools in Kuwait have been measured and found 17 Bq m −3 after subtracting the control (Maged 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The present study during the years 2013-2015, revealed a direct proportion of pollution from cars with that of the corresponding car parks, automobiles on the road and the recent rise of population in Kuwait. Studies [13,17,21] reported the effects of radon concentrations in indoor and outdoor environment of Kuwait. Limitation to such studies attributed to the: (a) difficult technicalities involved in their assessment, (b) inaccessibility of sampling strategies in the public and, (c) unawareness to respiratory illness caused by radon and their progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [15,18,19,20] showed high radon concentrations in the basement of buildings (58 Bq/m 3 ) than the first and second floors (29 Bq/m 3 and 15 Bq/m 3 ) respectively. However, Maged [21] observed the reverse phenomenon of radon concentrations variation in the first floor (16Bq/m 3 ) and the second floor (23.8Bq/m 3 ) of schools in Kuwait respectively, attributing to the lack of proper heating, ventilation, air-conditioning (HVAC) system and poor maintenance of the building at the second floor. Findings [22,23,24] confirmed the maintenance of a standard thermal comfort index for buildings occupants.…”
Section: Ah Bu-olayan and Bv Thomas Kuwait University Kuwaitmentioning
confidence: 99%
“…In educational institutions, Radon testing was carried out in 25 school buildings with similar building designs and HVAC systems over a period of 6 months with Track-Etch detectors. The results showed a mean Radon level of 16 ± 4 Bq/m 3 and alpha dose equivalent rate of 0.97 ± 0.25 mSv/yr (Maged, 2006). Another 2-year comparative indoor Radon gas assessment among a total of 150 schools and residential buildings was conducted in Kuwait by Al-Awadi and Khan (2018).…”
Section: Air Pollutants In Kuwaitmentioning
confidence: 99%